Campus sustainability in the Australian higher education sector: divergence and convergence in planning, reporting and tactics. Issue 1 (27th August 2021) - Melles, Gavin; Lodewyckx, Stefan; Hariharan, Thangatur Sukumar
Abstract : Purpose: This study provides a country-specific and sector-wide study of campus sustainability. Campus sustainability is a key consideration for the higher education (HEI) sector, and campus sustainability officers and managers manage its reporting and planning. Global and country-specific studies to date have focussed on individual organisation narratives, interviews with faculty and management and content analysis of reports and plans. Findings show wide divergence on scope and scale of formalised planning and reporting, few references to sustainability officers and managers' perspectives and limited reference to organisational theory to explain tactics and strategies adopted. As a result, there are a few country-specific and sector-wide studies. The purpose of this paper is to address the scarcity of country-specific and sector-wide studies into campus sustainability practices in HEI by combining qualitative and quantitative analysis. Design/methodology/approach: The authors provide the first sector-wide overview of formal campus sustainability commitments for the Australian public sector HEI ( n = 41) in terms of several key indicators – plans, reports and other indicators. Second, the authors use reflexive thematic analysis of interviews ( n = 21) with current and former sustainability officers and managers to examine sector organisational reasons for such variation. Third, the authors analyse HEI sector isomorphism and divergence on planning and reporting of campus sustainability from the perspective of institutional theory of organisations. Findings: This study finds some convergence on the need for plans, reporting and other engagement elements, albeit without any sector-wide standards being followed. The authors observe a trend towards carbon-neutral (CN) declarations before 2030 although with nuances on emissions scope and increasing inclusion of renewable energy. Interviews identify a range of strategies and tactics adopted for campus sustainability relative to internal and external organisational pressures. Overall, the sector still exhibits weak institutionalisation of sustainability. Research limitations/implications: This study interviews a specific and limited cohort ( n = 21) and presents an overview of sector reporting, planning and target setting although not a detailed content analysis. Other interview cohorts may have different views on the strategic and tactical purposes of reporting practices, and more in-depth analysis of formal plans and reports should be conducted in the future. Practical implications: This study concludes that the Australian HEI sector should consider greater public transparency of its data and reporting actions. Common standards and a benchmarking platform for the sector would improve overall engagement with all internal and external stakeholders. At present, the HEI sector's message to its key internal and external stakeholders is mixed and needs to change towards a more in-depth institutionalisation of sustainability on campus. Originality/value: Particular insights are the value of organisational strategies and tactics as an interpretive framework for HEI campus sustainability and how interviewees attribute sector competitors and self-different motives and tactics. Albeit limited, this is the first mapping of sector approaches to sustainability reporting and planning.